Socio-economic and Environmental Concerns of Water Resources Management in the Tana Basin, Kenya - Agwata, Jones; Abwao, Peter (School of Environmental Studies and Human Science, Kenyatta University, 2007)
Water is an essential resource for the development of any country and its availability is the most limiting factor for socio-economic progress and advancement. Due to various factors, there is a growing need for more water such that to address the increasing needs in both rural and urban areas, water projects are being developed to ensure water availability for various competing demands. However,most of the water projects are environmentally unsustainable. There is need therefore to institute an integrated approach for sustainable management of water resources.